AVALIAÇÃO PÓS OCUPAÇÃO: ESTUDO DE CASO DE UMA ESCOLA MUNICIPAL DE ENSINO FUNDAMENTAL EM VIAMÃO,RS - Ransolin, Natália; Sartori, Gabriela; Matos, Rafaela Schumacher de Campos; Sattler, Miguel Aloysio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present study describes a post occupancy evaluation developed at Frei Pacífico Municipal School for Elementary Education, located in the city of Viamão (RS - Brazil), ten years after its inauguration. The school project was designed using several principles of sustainability. Low impact alternatives associated to materials, waste treatment, green roofs and thermal comfort were employed. The performance evaluation included four phases: a walkthrough, which is characterized by a visit to collect information on the state of the building; interviews, to understand the operation of the school; questionnaire application on a sample of students, teachers and staff, besides activities with students from the early year; and, finally, project analysis, comparing it with what was effectively built. The evaluation showed: a) what sustainability strategies, originally proposed in its design were not implemented in the school construction, and how this resulted in a reduction in the users satisfaction; and b) How the lack of maintenance compromised the overall school performance.